Post-transplant lymphoproliferative disorder treated with rituximab and sirolimus: case report and review of literature - Pádua Netto , Marcus Vinícius de; Lima , Henrique Vieira de; Costa , Émerson Nunes; Pádua Netto, Luiz Cláudio; Borges , Ana Paula de Souza; Santos , Eduardo Moreira dos (Brazilian Journal of Transplantation, 2007)
Despite the benefits of the immunosuppressive medications to improve the graft function, they present several adverse effects, such as development of post-transplant lymphoproliferative disorder in renal transplant recipients needing sometime a drastic reduction or withdrawal of the Immunosuppression and the consequent risk for graft rejection. We report a 20-year-old white man with chronic renal failure diagnosis secondary to Plune Belly Syndrome that started hemodialisys therapy in 2004, and after six months, his mother offered to donate a kidney to him; he was treated with Tacrolimus, Mofetil Mycophenolate and Prednisone. Four months later, a post-transplant lymphoproliferative diagnosis was made, and the Tacrolimus and Mofetil Mycophenoplate were suddenly discontinued. There was no response, and Rituximab was associated, when the computed tomography showed regression of splenomegaly and remission of the lymphadenomegaly. Based on the benefit reported in the literature, Sirolimus was associated to Prednisone in the Immunosuppression maintenance.